2008
DOI: 10.1152/ajpendo.00463.2007
|View full text |Cite
|
Sign up to set email alerts
|

Mice with chronically increased circulating ghrelin develop age-related glucose intolerance

Abstract: Reed JA, Benoit SC, Pfluger PT, Tschö p MH, D'Alessio DA, Seeley RJ. Mice with chronically increased circulating ghrelin develop age-related glucose intolerance. Am J Physiol Endocrinol Metab 294: E752-E760, 2008. First published February 12, 2008 doi:10.1152/ajpendo.00463.2007.-Ghrelin is a gut peptide that stimulates food intake and increases body fat mass when administered centrally or peripherally. In this study, ghrelin was overexpressed in neurons using the neuron-specific enolase (NSE) promoter sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 33 publications
(64 reference statements)
0
28
1
Order By: Relevance
“…Ghrelin administration to rodents dose-dependently increases fasting blood glucose, lowers insulin levels, and attenuates insulin responses during glucose tolerance testing (15,16). Similar ghrelin-mediated effects on blood glucose and/or insulin release have been demonstrated in isolated rodent islets and pancreata, in ghrelin-overexpressing mice, and in humans (3,6,15,16,47). Ghrelin also directly stimulates glucagon secretion from pancreatic ␣-cells (5).…”
Section: Discussionmentioning
confidence: 93%
“…Ghrelin administration to rodents dose-dependently increases fasting blood glucose, lowers insulin levels, and attenuates insulin responses during glucose tolerance testing (15,16). Similar ghrelin-mediated effects on blood glucose and/or insulin release have been demonstrated in isolated rodent islets and pancreata, in ghrelin-overexpressing mice, and in humans (3,6,15,16,47). Ghrelin also directly stimulates glucagon secretion from pancreatic ␣-cells (5).…”
Section: Discussionmentioning
confidence: 93%
“…Acetic acid was added to each solution to adjust the final concentration to 1 M before tissue homogenization. We determine the tissue ghrelin concentration in supernatants obtained after centrifugation by radioimmunoassay (RIA) using anti-ghrelin [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] (C-RIA) and anti-ghrelin [1][2][3][4][5][6][7][8][9][10][11] (N-RIA) antisera, as described previously (12,15).…”
Section: Measurement Of Plasma and Tissue Ghrelin Concentrationsmentioning
confidence: 99%
“…Although several studies have demonstrated contradictory results (1,5,11,18,24), data from genetically engineered mice are consistent with this concept. Chronic elevation of plasma ghrelin levels suppresses insulin secretion, inducing glucose intolerance in transgenic mice (2,13,21), whereas ablation of ghrelin improves glucose tolerance by enhancing insulin secretion in diet-induced obesity (7) or ob/ob mouse models (23).…”
mentioning
confidence: 99%
“…These findings therefore suggest that ghrelin signaling contributes minimally to glucose homeostasis, at least during prolonged exposure to low-fat diet conditions. In contrast, transgenic mice with neuron-specific (and to a much lesser extent liver-specific) overexpression of ghrelin developed glucose intolerance at 32 weeks of age despite having lower body weights (96).…”
Section: Ghrelin and Pyy: Current Evidence From Mouse Mutagenesismentioning
confidence: 93%
“…Besides, Sun et al (114) crossed leptin deficient (ob/ob) mice with mice deficient in ghrelin to study the interaction of ghrelin and leptin signaling. Moreover, two recent studies described 1) a specific impairment of GHSR activation in the hypothalamus of rats (109) and 2) transgenic overexpression of ghrelin driven by the neuron-specific enolase promotor in mice (96). Such modulation of ghrelin function in the hypothalamus, a well-known central regulator of energy homeostasis, provides useful knowledge to dissect central versus peripheral actions of ghrelin.…”
Section: Ghrelin and Pyy: Current Evidence From Mouse Mutagenesismentioning
confidence: 99%